2005
DOI: 10.1002/ps.1117
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of herbicides to non‐target aquatic plants and algae: assessment of predictive factors and hazard

Abstract: Widely used herbicides sometimes inadvertently contaminate surface waters. In this study we evaluate the toxicity of herbicides to aquatic plants and algae and relate it to environmental herbicide concentrations and exposure scenarios, herbicide formulation and mode of action. This was done experimentally for ten herbicides, using the aquatic macrophyte Lemna minor L. and the green alga Pseudokirchneriella subcapitata (Korshikov) Hindak, supplemented with a database study comprising algae toxicity data for 146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 28 publications
9
79
0
2
Order By: Relevance
“…The variation between the controls expressed as the coefficient of variation (CV) of the controls was 8.3% for algae, 9.7% for duckweed, and 48.9% for lettuce. These variations are within the range reported in the literature [4,28,34]. The EC10 and EC50 values are listed in Table 1.…”
Section: Phytotoxicitymentioning
confidence: 62%
See 1 more Smart Citation
“…The variation between the controls expressed as the coefficient of variation (CV) of the controls was 8.3% for algae, 9.7% for duckweed, and 48.9% for lettuce. These variations are within the range reported in the literature [4,28,34]. The EC10 and EC50 values are listed in Table 1.…”
Section: Phytotoxicitymentioning
confidence: 62%
“…The effect of cyclotides on duckweed (L. minor) growth was conducted following the procedure described by Cedergreen and Streibig [28]. The concentrations and number of replicates were similar to the algae setup, apart from using 12 rather than eight replicates for the control treatment.…”
Section: Preventing Sorption Of Cyclotidesmentioning
confidence: 99%
“…Microalgae and crustaceans were four to five-fold more sensitive to Roundup than bacteria and protozoa. Effects of glyphosate and commercial formulations on plants and algae have been reported in the literature (Sáenz et al, 1997;Ma et al, 2002;Cedergreen and Streibig, 2005;Agritox, 2006;Ma et al, 2006;Pettersson and Ekelund, 2006;Toxnet, 2006). The toxicity of glyphosate has also been studied in a range of organisms including fish (salmon, trout, catfish), aquatic invertebrates (daphnids, midge's larvae) and ciliated protozoa (T. thermophila, Ichthyophthirius multililiis) (Folmar et al, 1979;Servizi et al, 1987;Mann and Bidwell, 1999;Everett and Dickerson, 2003;Agritox, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some works showed that 10 % of reduction (EC 10 ) could be reached between 3 to 16 folds lower concentrations than EC 50 . For instance, 10% growth inhibition in the green algae Scenedesmus subpicatus was observed in treatments with 1.6 mg/L of glyphosate acid (Vedrell et al, 2009 (Cedergreen & Streibig, 2005). Lower differences in toxicity were registered by other authors (e.g.…”
Section: Effects On Non-target Aquatic Plants and Algaementioning
confidence: 91%
“…Numerous contributions have demonstrated that inert ingredients in glyphosate formulations have several folds higher toxicity on non-target organisms than glyphosate alone (e.g. Folmar et al 1979;Wan et al 1989;Cedergreen & Streibig, 2005; among others). Therefore, glyphosate formulations are chemical mixtures and must be considered as mixtures in toxicity assessments.…”
Section: Commercial Formulations Of Glyphosatementioning
confidence: 99%